Single-nucleus ribonucleic acid-sequencing and spatial transcriptomics reveal the cardioprotection of Shexiang Baoxin Pill (SBP) in mice with myocardial ischemia-reperfusion injury - Lin, Wenyong; Chen, Xin; Wang, Dongyuan; Lu, Ruixia; Zhang, Chunling; Niu, Zhenchao; Chen, Jie; Ruan, Xiaofen; Wang, Xiaolong (Frontiers in Pharmacology, 2023)
Aim: The Shexiang Baoxin Pill (MUSKARDIA) has been extensively used to treat cardiovascular diseases in China for four decades, and its clinical efficacy has been widely approved. However, the mechanism by which this is achieved remains largely unexplored. Research attempting to understand the underlying mechanism is ongoing, but the findings are controversial. Here, we aimed to explore the possible mechanism of MUSKARDIA in myocardial ischemia-reperfusion (I/R) injury using heart single-nucleus and spatial ribonucleic acid (RNA) sequencing. Methods: We established a murine myocardial I/R injury model in C57BL/6 mice by ligating and recanalizing the left coronary artery anterior descending branch. Subsequently, single-nucleus RNA-seq and spatial transcriptomics were performed on mice heart tissue. We initially assessed the status of cell types and subsets in the model administered with or without MUSKARDIA. Results: We used single-nucleus RNA sequencing to comprehensively analyze cell types in the heart tissue of sham-operated, I/R, and MUSKARDIA mice. Nine samples from nine individuals were analyzed, and 75,546 cells were obtained. We classified the cells into 28 clusters based on their expression characteristics and annotated them into seven cell types: cardiomyocytes, endothelial cells, fibroblasts, myeloid cells, smooth muscle cells, B cells, and T cells. The MUSKARDIA group had distinct cellular compositions and features than the I/R group. Furthermore, MUSKARDIA-induced cardioprotection against I/R was associated with enhanced cardiac contractility, reduced endocardial cell injury, increased capillary network formation, and inhibited fibroblast proliferation. In addition, macrophages had active properties. Conclusion: Here, we comprehensively analyzed the cardioprotective effects of MUSKARDIA on myocardial I/R injured hearts using single-nucleus RNAsequencing and spatial transcriptomics-sequencing. Our study identified several candidate target genes and pathways. This is the first study to report the cellular landscape of a complex Traditional Chinese Medicine compound to explore myocardial I/R injury and MUSKARDIA-specific expression changes at the single-cell level and spatial resolution.